ANALISIS ANTREAN SPBU UDAYANA DENGAN MODEL ANTREAN NON-POISSON - PANDIANGAN, LUIS RICARDO; ASTUTIK, NI PUTU DIAN; LEMBUNAI, EVARISTUS VERIYOGI YALSCHEN; SRINADI, I GUSTI AYU MADE; OCTAVANNY, MADE AYU DWI (E-Jurnal Matematika, 2024)
Long queues at gas stations are a common sight, consuming valuable time for vehicle refueling. This inconvenience poses a challenge for the community, necessitating efficient time management. To address this issue, optimization through queue analysis is proposed. This study aims to analyze the queuing process for pertalite motorcycle fueling at one of the refueling stations, Udayana Gas Station, using the non-Poisson model (GPD/GEV/1):(FIFO/?/?). Additionally, a comparison is made with a modified scenario by introducing an extra server, resulting in the model (GPD/GEV/2):(FIFO/?/?). Based on 60 sampled data collected on Friday, 17 November, 2023, the analysis reveals a queue time of 5.8 minutes, with an expected 9 motorcycles in the queue. The results of the new model (GPD/GEV/2):(FIFO/?/?) indicate a notable reduction, with no motorcycles waiting in line for fueling. Consequently, it is recommended that Udayana Gas Station add an additional pertalite refueling station for motorcycles, promoting enhanced efficiency and convenience.